Influences of alcohol/polyols on interaction of moxifloxacin hydrochloride through cetyltrimethylammonium bromide at numerous temperatures and compositions. (2nd December 2021) - Chowdhury, Zahirul Islam; Khan, Javed Masood; Rana, Shahed; Mahbub, Shamim; Hossain, Md. Farhad; Rahman, Mohammad Majibur; Irfan, Mohammad; Ahmed, Mohammad Z.; Hoque, Md. Anamul; Anwar, SK Jahir
Abstract : A study on the interaction of a fourth-generation antibiotic drug, moxifloxacin hydrochloride (MFH), with a cationic surfactant, such as cetyltrimethylammonium bromide (CTAB) in the aqueous solution of alcohol (1-propanol (1-PrOH)) and polyols (galactose/maltose), has been carried out using the conductivity measurement technique. The critical micelle concentration ( cmc ), micelle ionisation ( α ), counter ion binding ( β ), and thermodynamic properties ( Δ G m 0, Δ H m 0, and Δ S m 0 ) for the self-aggregation of MFH + CTAB mixture have been estimated in 1-PrOH/polyols solutions. The presence of 1-PrOH delays the MFH + CTAB micelle formation, whereas polyols create a congenial environment for the micelle formation. In 1-PrOH, the values of α experience a reduction with the increase of 1-PrOH concentration and temperature. The values of α were found to be dependent on the concentration of other additives. In all of the cases thoroughly studied, the values of Δ G m 0 were found negative, which experience an enhancement in polyols solutions and decreased in 1-PrOH solution. On the basis of Δ H m 0 and Δ S m 0 values, the suggested interaction forces between MFH and surfactant are hydrophobic, ion-dipole, and electrostatic in nature. The values of Δ H m 0, ∗ reveal that the micelle is more stable in polyols media than that of the 1-PrOH medium. GRAPHICAL ABSTRACT: UF0001